Chapter Introduzione. La traduzione del linguaggio specialistico dei beni culturali: dalle pratiche passate alle metodologie attuali - Zotti, Valeria (Lessico multilingue dei Beni Culturali, 2023)
The Introduction presents the chronological evolution of the practices employed in the translation of the language of cultural heritage. All the Chapters in this volume share close ties with the objectives of the research project «Multilingual Cultural Heritage Lexicon» and follow three trajectories: 1. The translations of Vasari as primary sources for the origins of the lexicon of the arts in Europe 2. Considerations on translation praxis and teaching of different text types of cultural heritage 3. The latest developments in the compilation and use of translational corpora in relation to local heritage sites. Through a diachronic and a synchronic perspective, all chapters contribute to the existing literature on Corpus-based Translation Studies (CTS) of the language of cultural heritage.